Reassortant Clade 2.3.4.4 of Highly Pathogenic Avian Influenza A(H5N6) Virus, Taiwan, 2017 - Chen, Li-Hsuan; Lee, Dong-Hun; Liu, Yu-Pin; Li, Wan-Chen; Swayne, David E.; Chang, Jen-Chieh; Chen, Yen-Ping; Lee, Fan; Tu, Wen-Jane; Lin, Yu-Ju (Emerging infectious diseases, 2018)
A highly pathogenic avian influenza A(H5N6) virus of clade 2.3.4.4 was detected in a domestic duck found dead in Taiwan during February 2017. The endemic situation and continued evolution of various reassortant highly pathogenic avian influenza viruses in Taiwan warrant concern about further reassortment and a fifth wave of intercontinental spread.